Optimal prizes in dynamic elimination contests: Theory and experimental evidence - Rudi Stracke; Wolfgang Höchtl; Rudolf Kerschbamer; Uwe Sunde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
This paper investigates the implications of different prize structures on effort provision in dynamic (two-stage) elimination contests. Theoretical results show that, for risk-neutral participants, a structure with a single prize for the winner of the contest maximizes total effort, while a structure with two appropriately chosen prizes (a runner-up prize and a final prize) ensures incentive maintenance across stages. In contrast, a structure with two prizes may dominate a winner-takes-all contest in both dimensions if participants are risk-averse. Evidence from laboratory experiments is largely consistent with these predictions, suggesting that contest design should account for risk attitudes of participants.
Keywords: C72; D72; J33; 330; Dynamic Contests; Multiple Prizes; Risk Aversion; Experiment; Over-provision